Smart Bed Sheet Stretcher / Ezreen Ayu Khatijah Azman ... [et al.] - Azman, Ezreen Ayu Khatijah; Basori, Noor Izyana; Razak, Rushila Abdul; Zainol Ariffin, Siti Saudah; Wan Mohamed, Wan Ismahani (2018)
VINO Company has new product to introduce to the consumers which is the Smart Bed Sheet Stretcher. Our company is targeting in supply for bed stretcher since it is people morning routine to tidy up the bed sheet. Smart Bed Sheet Stretcher is a customer-friendly which Is. helps people saving time and ease to keep their bed sheet tidy. This study was conducted to develop a product that is automatic to tidy up messy bed sheet. It also discovers how many potential consumers are interested in the product. Also, this paper will highlight the design of the product and reasoning behind the special features chosen.